1989
DOI: 10.1152/jn.1989.61.1.218
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of passive membrane parameters with whole-cell recording from neurons in the intact amphibian retina

Abstract: 1. Whole-cell recordings have been obtained from intact, photoactive retinal neurons using patch-clamp electrodes in the amphibian superfused retina eyecup preparation. 2. After removal of the vitreous humor from the surface of the retina, using a collagenase with low tryptic activity, high-resistance seals (1-10 G omega) could be formed between the patch pipette and the cell membrane by applying mild suction to the pipette. Additional suction broke the membrane patch and provided continuity between the low-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
56
0
2

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 15 publications
10
56
0
2
Order By: Relevance
“…A previous compartmental model of an alpha cell (22) based on a low specific membrane resistance (2500 fl.cm2) suggested that nonlinear subunits correspond to discrete regions of the alpha dendritic tree. This scheme is unlikely, however, since the subunits coalesce into a single large subunit as the specific membrane resistance approaches currently published values (>8000 fQcm2) (19,20,22). A more plausible model is a rectifying amacrine cell interposed between the bipolar cell and the ganglion cell.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A previous compartmental model of an alpha cell (22) based on a low specific membrane resistance (2500 fl.cm2) suggested that nonlinear subunits correspond to discrete regions of the alpha dendritic tree. This scheme is unlikely, however, since the subunits coalesce into a single large subunit as the specific membrane resistance approaches currently published values (>8000 fQcm2) (19,20,22). A more plausible model is a rectifying amacrine cell interposed between the bipolar cell and the ganglion cell.…”
Section: Discussionmentioning
confidence: 90%
“…However, when the b1 surround is represented as an exponential (instead of a Gaussian), then the form of the alpha surround was indeed altered (Fig. 5D, heavy (13)(14)(15)(16)(17)(18)(19)(20) are opened by single quanta of transmitter at other central nervous system synapses (36,37). About 450 b, synapses contact the alpha cell (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of experiments examining iontophoretic responses, tetrodotoxin (0.5-1 1uM) was included to block sodium-dependent action potentials. Currents were recorded with an Axopatch 1B amplifier from neurons in the CA1 and CA3 pyramidal cell layers and granule cell layer of the dentate gyrus using the "blind" whole-cell recording technique (15,16 NaCI, pH 8). All experiments were performed at room temperature at a holding potential of -80 mV, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…In the majority of experiments examining iontophoretic responses, tetrodotoxin (0.5-1 1uM) was included to block sodium-dependent action potentials. Currents were recorded with an Axopatch 1B amplifier from neurons in the CA1 and CA3 pyramidal cell layers and granule cell layer of the dentate gyrus using the "blind" whole-cell recording technique (15,16 To measure glutamate desensitization, currents were recorded from outside-out patches pulled from the somata of pyramidal and granule neurons. Patches were maneuvered within the slice chamber to an apparatus constructed for the rapid application of agonists (6,8,17 solution containing kainate or glutamate to one containing the agonist but with a 10-fold lower concentration of NaCl (18).…”
Section: Methodsmentioning
confidence: 99%